Additions to the lichen flora of Araracuara (Colombian Amazonia) - Sipman Harrie J.M. (Caldasia, 1997)
Recent fieldwork in the primary vegetation around Araracuara (Colombian sector of Amazon Basin) showed the presence of a varied lichen flora in the forests and the savannahs on the sandstone table land. Here 93 species are recorded, mainly growing on tree bark, rock and soíl, raising the total number of known species from the area to 211. In spite of these additions the lichen flora is still supposed to be less than half-way known. Investigaciones recientes de campo en la vegetación primaria en los alrededores de Araracuara (sector Colombiano de la cuenca Amazónica) demostraron la presencia de una flora liquénica de gran variedad en los bosques y en las sabanas en las mesetas de arenisca. Se presentan 93 especies, principalmente en corteza, suelo y arenisca. En conjunto con las especies anteriormente publicadas, hace un total de 211 especies, cuyo número es probablemente menor que la mitad de la flora actual.